High-transmission acoustic self-focusing and directional cloaking in a graded perforated metal slab - Sheng-Dong Zhao (Nature Portfolio, 2017)
Abstract A design strategy and its modeling for high-transmission acoustic self-focusing and directional cloaking in a two-dimensional (2D) and an axisymmetric three-dimensional (3D) gradient-index phononic crystal (GRIN-PC) are reported in this paper. A gradient perforated aluminum slab sandwiched by water is considered. A low-loss directional cloaking device is achieved by controlling the matching coefficient between the slab and the water. The anisotropy coefficient that affects the scattering properties is also introduced. Furthermore, the phase discontinuity for directional cloaking inside and outside the slab is overcome by introducing a non-gradient slab having a lower group velocity behind the GRIN slab as an acoustic delay device. In addition, an axisymmetric 3D directional cloaking structure is obtained by rotating the corresponding 2D structure around the slab axis.